Effect of Nb Content and water quenching on microstructure and mechanical properties of Ti-Nb alloys fabricated by spark plasma sintering - Nattawood Suesawadwanid; Anak Khantachawana; Kasama Srirussamee; Katsuyoshi Kondoh (Powder Metallurgy, 2022)
Titanium-niobium (Ti-Nb) alloys have been extensively studied for medical implants due to their advantageous mechanical properties and biocompatibility. However, the stress shielding effect remains a challenge. This research investigated the effects of Nb content and enhancement of α′′ formation on the mechanical properties of Ti-xNb alloys (x = 0, 5, 15 and 25%) fabricated by spark plasma sintering. Water quenching from the β phase induced α′′ phase formation in Ti-5Nb and Ti-15Nb samples, thereby reducing their Young’s modulus values but was not observed in commercially pure titanium (CP-Ti) and Ti-25Nb. Results showed that heat treatment with water quenching induced α′′ phase formation and can be used to tailor the properties of Ti-Nb alloys fabricated by SPS. This technique can also be used to enhance material ductility at high β-stabilizer content, as observed in Ti-25Nb samples.
Keywords: Titanium Alloys Microstructure and Properties; Intermetallics and Advanced Alloy Properties; Advanced materials and composites